The Effect of Stunting on Children's Cognitive Development : Systematic Review - Nova Linda Rambe; Eva Nirwana Hutabarat; Rizki Hafifah (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The term stunting refers to an intellectual disorder characterized by mental abilities that reflect past nutritional status and a decline in development in children caused by chronic malnutrition. This can lead to stunted growth in children. Which can have a negative impact on the physical and mental development of children and subsequent learning abilities. Stunting is caused by various interacting factors, including poor sanitation and various other factors related to health, but the main cause is inadequate diet (total calories and essential nutrients), especially in the first 1,000 days. Malnutrition is an important determinant of maternal and child health, with significant negative effects on children's brain and cognitive development. This criterion uses original articles published in English and Indonesian. Articles published within the last 10 years. The review method uses a systematic review using PRISMA (Preferred Reporting Item for Systematic Review and Meta-analysis) with Systematic Review obtained from the Pubmed database, Scient direct, Wiley. This study went through four stages, namely identification, screening, feasibility and results received. This is so that the problem of stunting in children's cognitive development can be solved.Keywords: Child, Development cognitive, Stunting